Genomic Characterization of Clinical Listeria monocytogenes Isolates in Beijing, China - Zhang, Xiaoai; Liu, Yuzhu; Zhang, Penghang; Niu, Yanlin; Chen, Qian; Ma, Xiaochen (Frontiers in Microbiology, 2021)
Listeria monocytogenes is a foodborne human pathogen that affects public health worldwide. Whole-genome sequencing (WGS) can classify L. monocytogenes isolates and identify virulence islands and resistance genes potentially influencing infectivity. Herein, WGS was used to assess 151 L. monocytogenes isolates from 120 cases of clinical infection in Beijing, China, between 2014 and 2018. Most strains were either serogroup 1/2a,3a or serogroup 1/2b,3b,7, with 25 multilocus sequence typing (MLST) types(STs) represented, of which ST8, ST87 and ST5 were the most common. Core-genome MLST (cgMLST) grouped the 151 isolates into 116 cgMLST types. The discriminatory power of cgMLST was greater than other subtypes, revealing that isolates from the same patient were highly related (only differing at one allele). Eighty-six isolates formed 30 complexes with ≤ 7 cgMLST alleles between neighboring isolates, suggesting possible outbreaks. Compared with isolates in the United States, ST8, ST121, ST619, ST87 and ST155 isolates were grouped into unified clades. All 151 strains were positive for common virulence-associated loci, and 26 lineage I isolates harbored the pathogenicity island 3 (LIPI-3) locus, while 42 lineage isolates harbored the complete LIPI-4 locus. Eleven ST619 isolates had both LIPI-3 and LIPI-4. Among the 151 isolates, 13 were resistant to at least one antibiotic, and no multidrug-resistant isolates were identified. Resistance phenotypes correlated with genotypes, apart from two meropenem resistance isolates. The findings provide insight into the nature of L. monocytogenes strains currently causing clinical disease in Beijing, and WGS analysis indicates possible outbreaks.